Statement of Profit Loss of Pojok Cilira 46 - Ruth Glory Christin (Research Collaboration Community (RCC), 2020)
Warung Pojok Cilira 46 is a Micro, Small and Medium Enterprise (UMKM) which is engaged in the food sector. The sale of food and beverages is the main source of income for this restaurant. So far, roadside stall Pojok Cilira 46 still has difficulty analyzing the profit and loss from selling food and beverages. This study aims to assist in a more in-depth observation of the profits generated by lapak and losses obtained by lapak within a period of one month. In this report an analysis is carried out for the period January 3, 2020 – January 14, 2020. The method used in making this report is to use primary data by collecting observational data and interviews with shop owners related to the things needed in making a profit and loss report such as income, operational costs, assets and others. The results of this report show that sales in the first week of January, namely the period from January 3, 2020 to January 7, 2020, increased by 60% compared to the second week. It is hoped that this income statement can help in managing profits more optimally and the financial performance of Warung Pojok Cilira 46.